Neutrophil Cytosolic Factor 1 in Dendritic Cells Promotes Autoreactive CD8+ T Cell Activation via Cross-Presentation in Type 1 Diabetes - Liu, Chao; Whitener, Robert L.; Lin, Andrea; Xu, Yuan; Chen, Jing; Savinov, Alexei; Leiding, Jennifer W.; Wallet, Mark A.; Mathews, Clayton E. (Frontiers in Immunology, 2019)
Aims: Reactive oxygen species (ROS) are critical in driving the onset of type 1 diabetes (T1D). Ablation of ROS derived from phagocytic NADPH oxidase 2 (NOX2) is significantly protective against autoimmune diabetes in non-obese diabetic (NOD) mice. However, the mechanisms of NOX2-derived ROS in T1D pathogenesis need to be elucidated. Here, we have examined the role of NOX2 in dendritic cells (DC). Results: DC deficient in NOX2 exhibited reduced capacity to activate autoreactive CD8+ T cells. Instead of altering dendritic cell surface co-stimulatory molecule expression or promoting pro-inflammatory cytokine production, ROS promote CD8+ T cell activation by facilitating autoantigen cross-presentation. When provided with exogenous protein antigen, NOX2 deficient NOD DCs showed strong phagosome acidification and rapid antigen degradation, which lead to an absence of protein translocation into the cytoplasm and deficient antigenic peptide loading on MHC Class I molecules. Innovation: This study demonstrates that NOX2 is required for activation and effector function of CD8+ T cells by acting both intrinsically within the T cell as well as within professional antigen presenting cells. Conclusion: ROS scavengers could potentially represent an important component for therapies aiming to disrupt autoantigen presentation and activation of CD8+ T cells in individuals at-risk for developing T1D.